Does clinically measured walking capacity contribute to real-world walking performance in Parkinson's disease?. (December 2022) - Zajac, Jenna A.; Cavanaugh, James T.; Baker, Teresa; Duncan, Ryan P.; Fulford, Daniel; Girnis, Jaimie; LaValley, Michael; Nordahl, Timothy; Porciuncula, Franchino; Rawson, Kerri S.; Saint-Hilaire, Marie; Thomas, Cathi A.; et al.
Abstract: Objective: The study examined how clinically measured walking capacity contributes to real-world walking performance in persons with Parkinson's disease (PD). Methods: Cross-sectional baseline data (n = 82) from a PD clinical trial were analyzed. The 6-Minute Walk Test (6MWT) and 10-Meter Walk Test (10MWT) were used to generate capacity metrics of walking endurance and fast gait speed, respectively. An activity monitor worn for seven days was used to generate performance metrics of mean daily steps and weekly moderate intensity walking minutes. Univariate linear regression analyses were used to examine associations between each capacity and performance measure in the full sample and less and more active subgroups. Results: Walking capacity significantly contributed to daily steps in the full sample (endurance: R 2 =.13, p < .001; fast gait speed: R 2 =.07, p = .017) and in the less active subgroup (endurance: R 2 =.09, p = .045). Similarly, walking capacity significantly contributed to weekly moderate intensity minutes in the full sample (endurance: R 2 =.13, p < .001; fast gait speed: R 2 =.09, p = .007) and less active subgroup (endurance: R 2 = .25, p < .001; fast gait speed: R 2 =.21, p = .007). Walking capacity did not significantly contribute to daily steps or moderate intensity minutes in the more active subgroup. Conclusions: Walking capacity contributed to, but explained a relatively small portion of the variance in, real-world walking performance. The contribution was somewhat greater in less active individuals. The study adds support to the idea that clinically measured walking capacity may have limited benefit for understanding real-world walking performance in PD. Factors beyond walking capacity may better account for actual walking behavior. Highlights: Persons with PD demonstrate reduced amount and intensity of real-world walking. Clinical walking tests are often used to make inferences about real-world walking. Clinical walking tests were modest contributors to real-world walking. Walking capacity measures alone are not surrogates of real-world walking.